Diabetes risk status and physical activity in pregnancy: U.S. BRFSS 2011, 2013, 2015, 2017 - Bethany G. Rand; Tammie M. Johnson; Samantha F. Ehrlich; Laurie Wideman; James M. Pivarnik; Michael R. Richardson; Michelle L. Stone; James R. Churilla (BMC, 2020)
Abstract Background Pregnant women without complications are advised to engage in physical activity (PA) to mitigate adverse outcomes. Differences may exist among pregnant women of diverging diabetes status in meeting national PA recommendations. We sought to examine differences in aerobic activity (AA) and muscle strengthening activity (MSA) by diabetes risk status (DRS) among pregnant women in the United States. Methods The sample (n = 9,597) included pregnant women, age 18-44 years, who participated in the 2011, 2013, 2015, and 2017 Behavioral Risk Factor Surveillance System. Levels of DRS include: no diabetes (ND), high risk for diabetes (HRD) due to self-reported gestational diabetes or pre-diabetes, and overt diabetes due to self-reported, clinically diagnosed diabetes (DM). Odds ratios (ORs) and 95% confidence intervals (CI) for meeting PA recommendations were obtained. Covariates included age, race, education, household child count, alcohol consumption, and smoking status. Results Findings revealed that on average, DM had 46.5 fewer minutes of weekly AA compared to ND. Furthermore, a significantly lower OR (0.39; CI 0.19-0.82) for meeting both recommendations was observed in DM as compared to ND after adjustment. Conclusions We observed that pregnant women with overt diabetes had a lower odds of engaging in PA, while those at high risk were similar in their PA engagement to ND. Future studies aimed at assessing determinants of PA behavior may help guide efforts to promote exercise in pregnant women with diabetes.